2013
DOI: 10.1007/s00467-013-2539-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of galactose on glomerular permeability and proteinuria in steroid-resistant nephrotic syndrome

Abstract: Galactose decreases FSPF in children with SRNS, with the most significant improvement in those with post-transplant FSGS recurrence, but it fails to improve proteinuria. At the present time there is no evidence to support the use of galactose in children with FSGS, either pre- or post-transplant. Future studies to investigate the role of galactose as preemptive therapy to decrease the risk of post-transplant FSGS recurrence may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 8 publications
1
40
1
1
Order By: Relevance
“…We are in agreement with many of the points noted in the letter and have discussed them in our manuscript. The in vitro studies of Savin et al [1], as well as the case reports by Kopac [2] and De Smet [3], were the catalyst for undertaking this investigation, and are reviewed in our manuscript [4]. The authors state that the lack of response to galactose in our study may be due to preexisting permanent irreversible glomerular damage; we agree with this, and have delineated this as a possible explanation in our discussion section.…”
supporting
confidence: 70%
“…We are in agreement with many of the points noted in the letter and have discussed them in our manuscript. The in vitro studies of Savin et al [1], as well as the case reports by Kopac [2] and De Smet [3], were the catalyst for undertaking this investigation, and are reviewed in our manuscript [4]. The authors state that the lack of response to galactose in our study may be due to preexisting permanent irreversible glomerular damage; we agree with this, and have delineated this as a possible explanation in our discussion section.…”
supporting
confidence: 70%
“…Small case series suggest limited efficacy of Acthar in some individuals with FSGS (117,118) as has been reviewed (119); a randomized, controlled trial is in progress. Galactose, proposed as therapy for recurrent FSGS, has been shown to lack efficacy in steroid-resistant primary FSGS in children (120). Sirolimus may accelerate progression of FSGS and should be avoided (93).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…While some case reports have described remission after galactose treatment, a prospective study did not demonstrate any change in proteinuria after 16 weeks of therapy in seven children with steroid-resistant NS [74,75]. A recently completed phase II study (Novel Therapies for Resistant FSGS-FONT II) randomized seven adult and pediatric patients to galactose and found that three achieved a reduction in proteinuria by 50 % at 26 weeks of therapy [76].…”
Section: Emerging Therapiesmentioning
confidence: 97%